PENGARUH SIKAP MOTIVASI DAN LINGKUNGAN TERHADAP NIAT BERWIRAUSAHA (STUDI PADA MAHASISWA PERGURUAN TINGGI DI WILAYAH KABUPATEN SUKOHARJO) - Agesti Indah Fransisca; Bambang Nur Cahyaningrum; Yoppi Syahrial (Journal Of Business, Finance, and Economics (JBFE), 2021)
This study aims to determine the effect of attitude, motivation, and environment on entrepreneurial intentions. The sample of this study were active undergraduate students (S1) of tertiary institutions in the Sukoharjo Regency. With the number of respondents 86 people. The analytical tool used to determine the effect between the independent and dependent variables using SPSS. Hypothesis testing in this study uses multiple linear analysis. Based on the results of the analysis showed that the variables of attitude, motivation have a positive and significant effect on entrepreneurial intentions. Meanwhile, environmental variables do not significantly influence to entrepreneurial intentions. Keywords: attitude, motivation, environment, and entrepreneurial intention